Traceability of primordial germ cells in three neotropical fish species aiming genetic conservation actions - Rosero, Jenyffer; Monzani, Paulo Sérgio [UNESP]; Pessoa, Giselle Pessanha [UNESP]; Coelho, Geovanna Carla Zacheo [UNESP]; Carvalho, Gabriella Braga; López, Lucia Suárez [UNESP]; Senhorini, José Augusto [UNESP]; dos Santos, Silvio Carlos Alves; Yasui, George Shigueki (Springer Nature, 2024)
Primordial germ cells (PGCs) are embryonic pluripotent cells that can differentiate into spermatogonia and oogonia, and therefore, PGCs are a genetic source for germplasm conservation through cryobanking and the generation of germline chimeras. The knowledge of PGC migration routes is essential for transplantation studies. In this work, the mRNA synthesized from the ddx4 3′UTR sequence of Pseudopimelodus mangurus, in fusion with gfp or dsred, was microinjected into zygotes of three neotropical species (P. mangurus, Astyanax altiparanae, and Prochilodus lineatus) for PGC labeling. Visualization of labeled PGCs was achieved by fluorescence microscopy during embryonic development. In addition, ddx4 and dnd1 expressions were evaluated during embryonic development, larvae, and adult tissues of P. mangurus, to validate their use as a PGC marker. As a result, the effective identification of presumptive PGCs was obtained. DsRed-positive PGC of P. mangurus was observed in the hatching stage, GFP-positive PGC of A. altiparanae in the gastrula stage, and GFP-positive PGCs from P. lineatus were identified at the segmentation stage, with representative labeling percentages of 29% and 16% in A. altiparanae and P. lineatus, respectively. The expression of ddx4 and dnd1 of P. mangurus confirmed the specificity of these genes in germ cells. These results point to the functionality of the P. mangurus ddx4 3′UTR sequence as a PGC marker, demonstrating that PGC labeling was more efficient in A. altiparanae and P. lineatus. The procedures used to identify PGCs in P. mangurus consolidate the first step for generating germinal chimeras as a conservation action of P. mangurus.
Keywords: Characiformes; ddx4; Micromanipulation; Ontogenetic development; PGC; Siluriformes